Eficácia dos direitos humanos nas relações privadas empresariais em uma perspectiva de vinculação multinível: o dever de respeito à pessoa humana - Leonel, Ana Leticia Anarelli Rosati (Universidade do Vale do Rio dos Sinos, 2021)
Although there are already guidelines and recommendations on the need for companies to respect human rights, there are, in fact, huge and growing violations that impact the lives of many people, especially when it comes to a transnational company and its complex structure. And if, on the one hand, the number of cases grows, it is necessary to think about the increase and growth of the accountability of such companies, distancing from a history of existing impunity. Therefore, it is important to ask under which conditions the compatibility between the imposition of binding norms, the guiding principles of Human Rights and Companies, elaborated by John Gerard Ruggie, as well as the strength of social movements, can present a coherent construction and ensure the effectiveness of enforcement and respect for human rights by national or multinational business societies. In this regard, thinking about isolated options that are available so that, in fact, protections to human beings are effective, has contributed little, until now, with the decrease in the number of violations. Therefore, it is necessary to think about the possibility and measure of the effectiveness of human rights in private relations, taking into account, basically, the need for human rights to also oblige different transnational private actors, especially companies, through distinct conceptions: from top to bottom, collaterally and from bottom to top. In other words, it is necessary to think about a multisite impact on the demand for respect for such rights, so that companies are subject to three levels of pressure on their activities, considering state power, the cooperation that they must perform with other private actors, such as companies that have relations of any kind and, finally, also considering the very manifestations of the society in which the company is inserted.
Keywords: Direitos humanos; Empresas; Eficácia; Responsabilização; Human rights; Companies; Efficiency; Accountability; ACCNPQ::Ciências Sociais Aplicadas::Direito